KOORDINASI MATA KAKI, KESEIMBANGAN, KELINCAHAN, DAN KETERAMPILAN MENGGIRING DALAM SEPAK BOLA - Mappaompo, Adam (Indonesian Journal of Educational Studies, 2015)
This study aims to determine the relationship together eye-foot coordination, balance, and agility with dribbling skills in the game of football. This research is a descriptive study with a sample of 30 players. Data were analyzed using correlation analysis. The results showed that (1) there is a significant correlation eye-foot coordination with dribbling skills with Ï value of -0.622 (pvalue <0.05); (2) there is a significant relationship keseimbangandengan dribbling skills with Ï value of -0.648 (pvalue <0.05); (3) there is a significant relationship with the agility skills of dribbling with Ï value of 0,747 (pvalue <0.05); (4) there is a significant relationship together eye-foot coordination, balance, and agility with dribbling skills with the R value of 772 (pvalue <0.05).